Virtual Tourism as a Tool for Improving Learners Tour Guiding Skills - Mendoza, Ann Loise I. (International Journal of Research in Interdisciplinary Studies, 2025)
Virtual Tourism has paved its way in both the education and tourism industry as a result of travel restrictions during the pandemic, yet not long after the lockdowns were lifted, the idea of using technology in platforms like tourism has remained. Virtual environments have always been affected by three factors, immersion, presence and interactivity, which showed great effects on learners’ performance, especially in courses requiring high levels of communication skills like in tour guiding. A single group experimental study, involving forty (40) Grade 8 learners of San Jose Integrated High School S.Y. 2024-2025, taking up Tourism Promotion Services as the respondents, aiming to determine whether the application of virtual tourism as a tool would improve learners tour guiding skills as per their communication skills was created. Both pre-test and post-test administered to the respondents showed a notably high increase after the intervention was done. The results revealed that after being exposed to the virtual application the level of tour guiding skills of learners as per their communication skills under the following factors – building rapport, being informative, resolving conflict, creating a positive experience and promoting tourism product has significantly increased, with p<0.000 in all aspects. And furthermore, these results have revealed a great potential for virtual tourism as a tool for an improved learners’ tour guiding skills, equipping them to face real-world tour situation with ease and confidence.